Analysis of ice load on conical structure with discrete element method. Issue 4 (15th June 2015) - Y.T. Feng, Professor Xikui Li, Professor Yuangqiang Tan and Professor Shunying Ji, Professor; Ji, Shunying; Di, Shaocheng; Liu, Shewen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In oil/gas exploitations of ice-covered cold regions, conical offshore structures are designed to reduce ice force and to avoid the ice-induced intense vibrations of vertical structures. The purpose of this paper is to investigate the interaction between ice cover and conical offshore structures, the discrete element method (DEM) is introduced to determine the dynamic ice loads under different structure parameters and ice conditions. Design/methodology/approach – The ice cover is dispersed into a series of bonded spherical elements with the parallel bonding model. The interaction between ice cover and conical offshore structure is obtained based on the DEM simulation. The influence of ice velocity on ice load is compared well with the experimental data of Hamburg Ship Model Basin. Moreover, the ice load on a conical platform in the Bohai Sea is also simulated. The ice loads on its upward and downward ice-breaking cones are compared. Findings – The DEM can be used well to simulate the ice loads on conical structures. The influences of ice velocity, ice thickness, conical angle on ice loads can be analyzed with DEM simulations. Originality/value – This DEM can also be applied to simulate ice loads of different offshore structures and aid in determining ice load in offshore structure designs.